Efforts to Strengthen and Protect Customary Land in Lampung - Muhammad Daffa Hakim (Terekam Jejak Publisher, 2026)
Customary land for the Lampung Pepadun community has a meaning that is more than just an economic asset, but also reflects the identity, spirituality, and socio-cultural system inherent in the life of the community. In the Lampung Pepadun traditional view, land is